Factors in school leaving variations across gender groups, school levels and locations - Nava, Fe Josefa G. (Education Quarterly, 2009)
The effect of poverty on school leaving was examined for various gender groups, school levels and school locations based on interview data of dropouts (n=38), parents of dropouts (n=18), teachers (n=13) and school administrators of 4 purposively selected elementary and secondary schools in urban and rural locations. By segregating responses according to gender, school level and location of respondents, specific factors related to school level were identified for male and female, elementary and secondary, and urban and rural school dropouts. Employment activities were common among older dropouts, especially the males, while domestic duties such as caring for younger siblings were most true of females, especially those from rural areas. Low motivation was also evident among male and younger school dropouts.